Analisis Yuridis Akta Pernyataan Nafkah Terhadap Istri dan Anak Yang Dibuat di Hadapan Notaris (Studi Putusan MA RI No.3002/K/Pdt/2015) - rita sh,mkn (Universitas Harapan Medan, 2021)
A divorce is not a goal in a marriage; however a marriage sometimes ends with it, as experienced by AH and YR. YR filed a lawsuit against her husband AH to Muara Enim District Court after a divorce. YR felt financially injured by the action of AH for having violated the content of Statement Deed No.72 dated November 23, 2012 concerning Ah’s obligations to provide support for her and their children after their divorce took place. At District Court level, the judge in Ruling No.14/PDT.G/2014/PN.ME dated August 19, 214 granted parts of YR’s lawsuit. The judge stated that the Statement Deed is valid before the law, and is more valid by the issuance of the Higher Court Ruling No.114/PDT/2014/PT.PLG; which strengthens the District Court Ruling. However, the judge at cassation level granted the cassation application filed by AH. I the concern of the Supreme Court Judge, the Statement Deed is legally defective because it contradicts Article 45 paragraph (2) of the Marriage Act. The research problems are how about the legal force of the Deed of Statement to provide support for wife and child that was drawn up before a Notary, how about the legal consideration of the judge in the Supreme Court Verdict No.3002K/PDT/2015 and how about the legal liability of the Notary for the revocation of the Deed of Statement pursuant to the Supreme Court Verdict No.3002K/PDT/2015. Thic is a normative juridical research which analyzes the law, It employs descriptive analysis approach. The data are analyzed qualitatively. The Deed of Statement No.72 dated November 23, 2012, that was drawn up before Notray AD contains a statement of promise or a clause that does not fulfill the ojective requirements for an agreement. It bocomes null and void and has no legal force. It has been degraded in to an underhanded deed. The Supreme Court Verdict lacks of consideration because the judge was not sufficiently conscientious and has no evident legal ground. The degraded Statement Deed may become the ground to the injured party to file a lawsuit for indemnity such as compensation for all costs, fine and interests incurred to the Notray AD. It is suggested that a deed be carefully and conscientiously drawn up by noticing all prevailing legal aspects. It is recommended that judges have extensive knowledge, be update with the development of prevailing positive laws, so that they will produce responsible ruling with evident and obvious legal consideration. It is also suggested that notaries excercise their role well to provide legal certainty and legal protection for the person appeaering before them.